Energy renovation rates in the Netherlands – comparing long and short term prediction methods - Faidra Filippidou; Nina Holck Sandberg; Igor Sartori; Nico Nieboer; Magnus Inderberg Vestrum; Jan Sandstad Næss; Helge Brattebø (A+BE: Architecture and the Built Environment)
The building sector plays a major role in order to meet the energy saving targets set in the EU and the Netherlands (SER, 2013; ürge-Vorsatz et al., 2007). Existing buildings are responsible for 36% of the CO2 emissions in the European Union (EU) (European Commission, 2008 and 2014). Moreover, among the end use sectors – industry, transport, households, services, fishing, agriculture, forestry and non-specified – households represent one of the most energy intensive sectors consuming 24.8% of the total final energy (European Commission, 2016a; EEA 2017). Two major directives are currently in force, on an EU level, to tackle the issue of energy efficiency improvement of buildings – the Energy Efficiency Directive (EED) and the Energy Performance Buildings Directive (EPBD) (European Parliament, 2010, 2012). Improving the efficiency of the building stock is a central pillar for the carbon reduction goals of the member states (MS) and the EU as a whole.